Sealant and method for producing and using the same

CN122958983APending Publication Date: 2026-10-23TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510471104.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本申请实施例提供一种密封胶及其制备方法、应用,以解决或缓解上面提出的如何有效的阻隔盐雾进入光伏组件技术问题

Benefits of technology

[0006]本申请实施例提供一种密封胶及其制备方法、应用,以解决或缓解上面提出的如何有效的阻隔盐雾进入光伏组件技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application belongs to the field of solar cells and provides a sealing glue, a preparation method and application thereof. The sealing glue comprises polyorganosiloxane, fillers, cross-linking agents, coupling agents, catalysts, silicates and barrier agents, and the barrier agents comprise silane-modified magnesium hydroxide. The sealing glue of the application can be cured at room temperature, has good mechanical properties, bonding properties and aging resistance, and also has good salt mist barrier effect, which can provide good protection for solar photovoltaic products used on the sea.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solar cell technology, and in particular to a sealant, its preparation method, and its application. Background Technology

[0002] Solar photovoltaic (PV) power generation is a technology that directly converts light energy into electrical energy using the photovoltaic effect at semiconductor interfaces. The core component of solar PV power generation is the solar cell. However, due to inherent defects such as thinness, brittleness, and susceptibility to oxidation, solar cells are easily and permanently damaged when exposed to air, rain, and other natural environments. Therefore, to achieve the industrial application of solar power generation, protective sealing is required, such as forming solar photovoltaic modules.

[0003] Currently, when solar photovoltaic (PV) modules are used in the ocean, they face challenges including high salt spray, high UV radiation, and high humidity and heat. Silicone sealants, due to their superior resistance to high and low temperatures, weather resistance, and good adhesion and sealing properties, are particularly suitable for the protective sealing of solar cell modules. Although silicone sealants are resistant to salt spray corrosion, under prolonged salt spray conditions, chloride and sodium ions can easily penetrate the sealant itself and directly enter the module encapsulation, thus affecting the electrical performance of the solar cells.

[0004] Therefore, effectively preventing salt spray from entering the interior of photovoltaic modules and extending their service life is of great practical significance for the development and promotion of marine photovoltaic new energy products.

[0005] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the Invention

[0006] This application provides a sealant, its preparation method, and its application to solve or alleviate the technical problem mentioned above of how to effectively prevent salt spray from entering photovoltaic modules.

[0007] A first aspect of this application provides a sealant comprising: a polyorganosiloxane, a filler, a crosslinking agent, a coupling agent, a catalyst, a silicate, and a barrier agent, wherein the barrier agent comprises silane-modified magnesium hydroxide.

[0008] The sealant of this application can cure at room temperature and has good mechanical properties, adhesion properties and aging resistance. It also has a good effect in blocking salt spray and can provide good protection for solar photovoltaic products used at sea.

[0009] The silane-modified magnesium hydroxide in the barrier agent has a layered bimetallic oxide structure. Its layered structure forms a complex anti-permeation diffusion path, which significantly reduces the penetration of chloride and sodium ions into the sealant. At the same time, the anions between its layers are easily replaced by other anions, exhibiting good anion exchange performance. It can absorb chloride ions in the environment, thereby preventing chloride ion corrosion. The silane-modified magnesium hydroxide has good dispersibility in the silica gel system and can absorb polymers to form encapsulated structural units, improving the orderliness of the polymer structure. This, in turn, can reduce structural defects within the sealant system and better protect the internal battery of the component from corrosion by external chloride and sodium ions. Silicates possess a layered structure with a high specific surface area and a large aspect ratio at the microscopic level. When water vapor wants to pass through, it must bypass the filler, thus increasing the water vapor path and effectively hindering the diffusion and penetration of water molecules, reducing water permeability, and exhibiting excellent water-blocking effect. This significantly limits the permeability of chloride and sodium ions in water vapor to the colloid, improving the sealant's resistance to salt spray corrosion. The filler effectively compensates for the mechanical losses caused by silane-modified magnesium hydroxide. Polyorganosiloxanes participate in the cross-linking reaction, providing the main network structure. Cross-linking agents promote the degree of cross-linking between components. Coupling agents control the adhesive force of the system. Catalysts catalyze the system's reaction. Therefore, the synergistic effect of polyorganosiloxanes, fillers, cross-linking agents, coupling agents, catalysts, silicates, and barrier agents allows the sealant to cure at room temperature, exhibiting good mechanical properties, adhesion properties, and aging resistance, as well as excellent salt spray barrier properties, providing good protection for solar photovoltaic products used at sea.

[0010] According to an embodiment of this application, the sealant comprises, by weight, 40-60 parts of polyorganosiloxane, 26-46 parts of filler, 5-15 parts of barrier agent, 5-10 parts of silicate, 3-6 parts of crosslinking agent, 0.5-3 parts of coupling agent, 0.05-0.3 parts of catalyst, and the total amount of the sealant is 100 parts.

[0011] According to embodiments of this application, the polyorganosiloxane includes hydroxyl-terminated polydimethylsiloxane.

[0012] According to embodiments of this application, the filler includes at least one of calcium carbonate and silica.

[0013] According to embodiments of this application, the silicate includes at least one of kaolin, mica, and montmorillonite.

[0014] According to embodiments of this application, the crosslinking agent includes at least one of methyltributanone oxime silane, vinyltributanone oxime silane, and tetrabutanone oxime silane.

[0015] According to embodiments of this application, the coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and amino coupling agent oligomers.

[0016] According to embodiments of this application, the catalyst includes at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin dineodecanate.

[0017] According to embodiments of this application, the hydroxyl-terminated polydimethylsiloxane has a viscosity of 10,000-50,000 mPa·s.

[0018] According to embodiments of this application, the specific surface area of ​​the silica is 150-250 m². 2 / g.

[0019] According to an embodiment of this application, the calcium carbonate has a particle size of 60-100 nm.

[0020] According to embodiments of this application, the particle size of the silane-modified magnesium hydroxide is 1-10 μm.

[0021] According to embodiments of this application, the particle size of the silicate is 5-30 μm.

[0022] A second aspect of this application provides a method for preparing a sealant of the first aspect. The method includes: first mixing a polyorganosiloxane, a silicate, a barrier agent, and a filler to obtain a base material; second mixing the base material with the crosslinking agent to obtain a mixture; and third mixing the mixture with a coupling agent and a catalyst to obtain a sealant.

[0023] The method described in this application is simple to operate and can obtain a sealant with good performance. It involves first obtaining a base material, then mixing the base material with a crosslinking agent to obtain a mixture; finally, the mixture is combined with a coupling agent and a catalyst to obtain the sealant. In this method, the base material and crosslinking agent are first mixed evenly, and then the coupling agent and catalyst are added in stages. Firstly, the crosslinking agent needs the action of a catalyst to achieve crosslinking and curing. If the crosslinking agent, coupling agent, and catalyst are added simultaneously to prepare the sealant, crosslinking and curing may occur during prolonged stirring, making it difficult to obtain a qualified sealant and making it difficult to apply. According to an embodiment of this application, the temperature of the first mixture is 90-120°C.

[0024] According to an embodiment of this application, the vacuum degree of the first mixture is not higher than -0.095 MPa.

[0025] According to an embodiment of this application, the first mixing time is 1-3 hours.

[0026] According to an embodiment of this application, the second mixing time is 20-40 minutes.

[0027] According to an embodiment of this application, the vacuum degree of the third mixture is not higher than -0.095 MPa.

[0028] According to an embodiment of this application, the third mixing time is 20-40 minutes.

[0029] A third aspect of this application provides the application of the sealant of the first aspect or the sealant prepared by the method of the second aspect in the sealing of solar photovoltaic modules used at sea. This sealant has good salt spray barrier properties, providing good protection for solar photovoltaic products used at sea.

[0030] The sealant is used in the frame sealant part of offshore photovoltaic modules, filling the gap between the photovoltaic laminate and the profile to play a role in bonding and sealing. Detailed Implementation

[0031] The embodiments of this application are described in detail below. It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in orders other than those described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0032] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the distribution of selectable numerical values ​​within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The "numerical interval" can be broadly included to include quantitative intervals such as percentage intervals, ratio intervals, and proportion intervals.

[0033] In high-salt-spray environments, the entry of sodium chloride ions into solar photovoltaic modules causes severe chemical corrosion of the aluminum, lead oxide, and silver on the front of the cells. This leads to the replacement of glass frit and aluminum in the slurry by chloride and sodium ions, increasing the porosity of the slurry and ultimately damaging the electrical contacts of the cells. This significantly reduces the module's electrical performance and may even cause module failure. Existing silicone photovoltaic sealants primarily serve to seal and bond the frame of the modules. However, in long-term salt-spray environments, they are insufficient to block chloride and sodium ions from the outside of the module. Once these ions penetrate the module through the sealant, electrical performance is affected, and there is even a risk of failure. Therefore, improving the chloride and sodium ion blocking performance of silicone photovoltaic sealants and extending the module's lifespan is of significant practical importance for the development and promotion of offshore photovoltaic new energy products.

[0034] Accordingly, in a first aspect of the present application, a sealant is provided, the sealant comprising a polyorganosiloxane, a filler, a crosslinking agent, a coupling agent, a catalyst, a silicate, and a barrier agent, wherein the barrier agent comprises silane-modified magnesium hydroxide.

[0035] The sealant of this application can cure at room temperature and has good mechanical properties, adhesion properties and aging resistance. It also has a good effect in blocking salt spray and can provide good protection for solar photovoltaic products used at sea.

[0036] The silane-modified magnesium hydroxide in the barrier agent has a layered bimetallic oxide structure. Its layered structure forms a complex anti-permeation diffusion path, which significantly reduces the penetration of chloride and sodium ions into the sealant. At the same time, the anions between its layers are easily replaced by other anions, exhibiting good anion exchange performance. It can absorb chloride ions in the environment, thereby preventing chloride ion corrosion. The silane-modified magnesium hydroxide has good dispersibility in the silica gel system and can absorb polymers, thereby forming encapsulated structural units, improving the orderliness of the polymer structure, and thus reducing structural defects in the sealant system, better protecting the internal battery of the component from external chloride and sodium ion corrosion. Silicates possess a layered structure with a high specific surface area and a large aspect ratio at the microscopic level. When water vapor wants to pass through, it must bypass the filler, thus increasing the water vapor path and effectively hindering the diffusion and penetration of water molecules, reducing water permeability, and exhibiting excellent water-blocking effect. This significantly limits the permeability of chloride and sodium ions in water vapor to the colloid, improving the sealant's resistance to salt spray corrosion. The filler effectively compensates for the mechanical losses caused by silane-modified magnesium hydroxide. Polyorganosiloxanes participate in the cross-linking reaction, providing the main network structure. Cross-linking agents promote the degree of cross-linking between components. Coupling agents control the viscosity of the system. Catalysts catalyze the system's reaction. Therefore, the synergistic effect of polyorganosiloxanes, fillers, cross-linking agents, coupling agents, catalysts, silicates, and barrier agents allows the sealant to cure at room temperature, exhibiting good mechanical properties, adhesion properties, and aging resistance, as well as excellent salt spray barrier properties, providing good protection for solar photovoltaic products used at sea.

[0037] In some embodiments, the sealant, by weight, comprises: 40-60 parts of polyorganosiloxane, 26-46 parts of filler, 5-15 parts of barrier agent, 5-10 parts of silicate, 3-6 parts of crosslinking agent, 0.5-3 parts of coupling agent, and 0.05-0.3 parts of catalyst, and the total amount of the sealant is 100 parts. If the weight percentage of polyorganosiloxane is too high, it will affect the overall proportion of barrier agent and silicate, resulting in a poorer actual barrier effect; if it is too low, it will result in a low crosslinking density of the cured colloid and relatively poor mechanical properties. If the weight percentage of filler is too high, it will cause filler particles to aggregate, resulting in lower mechanical properties and poorer flowability of the colloid; if it is too low, it will be difficult to achieve the reinforcing effect of the filler, and the colloid strength will decrease. If the weight percentage of barrier agent is too high, it will lead to a decrease in the overall filler proportion and a decrease in colloid strength; if it is too low, it will be difficult to achieve a good barrier effect. If the weight percentage of silicate is too high, it will lead to a decrease in the overall filler proportion and a decrease in colloid strength. The strength is reduced; too low a concentration will make it difficult to achieve a good water-blocking effect. If the mass fraction of the crosslinking agent is too high, the crosslinking density will be too high, making the colloid too hard and brittle, thus reducing its flexibility and impact resistance. If it is too low, the colloid density will be too low, resulting in a decrease in strength. If the mass fraction of the coupling agent is too high, the viscosity of the colloid will increase, which is not conducive to flowability. If it is too low, the adhesive strength of the sealant will be insufficient. If the mass fraction of the catalyst is too high, the reaction will be too fast during the curing of the colloid, affecting product quality and shelf life. If it is too low, it will be difficult to control the curing time of the colloid within a reasonable range, affecting the actual application effect.

[0038] According to embodiments of this application, polyorganosiloxanes have the function of participating in cross-linking reactions and providing the main network structure.

[0039] In some embodiments, the polyorganosiloxane includes hydroxyl-terminated polydimethylsiloxane.

[0040] Furthermore, the hydroxyl-terminated polydimethylsiloxane has a viscosity of 10,000-50,000 mPa·s, such as 10,000 Pa·s, 20,000 Pa·s, 30,000 Pa·s, and 50,000 Pa·s. This improves the viscosity and formability of the sealant.

[0041] According to embodiments of this application, the filler effectively compensates for the mechanical losses caused by silane-modified magnesium hydroxide.

[0042] Optionally, the filler includes at least one of calcium carbonate and silica.

[0043] Furthermore, the calcium carbonate has a particle size of 60-100 nm, such as 60 nm, 70 nm, 80 nm, 100 nm, etc. This improves the viscosity and formability of the sealant.

[0044] Furthermore, the specific surface area of ​​silica is 150-250 m².2 / g, for example, 150m 2 / g、190m 2 / g、210m 2 / g、230m 2 / g、250m 2 / g etc. This can improve the viscosity and formability of the sealant.

[0045] According to an embodiment of this application, the silicate has a layered structure, which has a high specific surface area and a large aspect ratio at the microscopic level. When water vapor wants to pass through, it must bypass the filler, thereby increasing the path of water vapor.

[0046] Optionally, the silicate includes at least one of kaolin, mica, and montmorillonite.

[0047] Furthermore, the silicate has a particle size of 5-30 μm, such as 5 μm, 10 μm, 19 μm, 23 μm, 30 μm, etc. This improves the viscosity and formability of the sealant.

[0048] According to embodiments of this application, the barrier agent is used to block chloride ions and sodium ions in salt spray.

[0049] Optionally, the barrier agent includes silane-modified magnesium hydroxide.

[0050] Furthermore, the silane-modified magnesium hydroxide has a particle size of 1-10 μm, such as 1 μm, 4 μm, 6 μm, 8 μm, 10 μm, etc. This improves the viscosity and formability of the sealant.

[0051] In some embodiments, the crosslinking agent includes at least one of methyltributanone oxime silane, vinyltributanone oxime silane, and tetrabutanone oxime silane.

[0052] In some embodiments, the coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and amino coupling agent oligomers.

[0053] Furthermore, the amino coupling agent oligomer includes at least one of Hubei Jianghan New Materials JH-AP11, JH-AP1231, and JH-AP1234.

[0054] In some embodiments, the catalyst comprises at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin dineodecanate.

[0055] In some embodiments, the polyorganosiloxane, filler, crosslinking agent, coupling agent, catalyst, silicate, and barrier agent are combined with each other. The sealant of this application can be cured at room temperature and has good mechanical properties, adhesion properties, and aging resistance. It also has a good effect in blocking salt spray and can provide good protection for solar photovoltaic products used at sea.

[0056] Optionally, the sealant has a hardness of 48-53 shore A, such as 48 shore A, 49 shore A, 50 shore A, 51 shore A, 53 shore A, etc.

[0057] Optionally, the tensile strength of the sealant is 2-3 MPa, such as 2 MPa, 2.5 MPa, 3 MPa, etc.

[0058] Optionally, the tensile strength of the sealant is 280-400%.

[0059] Optionally, the sealant has a shear strength of 1.6-2.5 MPa, such as 1.6 MPa, 2.2 MPa, 2.5 MPa, etc.

[0060] A second aspect of this application provides a method for preparing a sealant of the first aspect. The method includes: (1) mixing a polyorganosiloxane, a silicate, a barrier agent, and a filler in a first mixing to obtain a base material; (2) mixing the base material with the crosslinking agent in a second mixing to obtain a mixture; and (3) mixing the mixture with a coupling agent and a catalyst in a third mixing to obtain a sealant.

[0061] The method described in this application is simple to operate and can produce a sealant with good performance. It involves first obtaining a base material, then mixing the base material with a crosslinking agent to obtain a mixture; finally, the mixture is combined with a coupling agent and a catalyst to obtain the sealant. In this method, the base material and crosslinking agent are first mixed evenly, and then the coupling agent and catalyst are added in stages. Firstly, the crosslinking agent needs the action of a catalyst to achieve crosslinking and curing. If the crosslinking agent, coupling agent, and catalyst are added simultaneously to prepare the sealant, crosslinking and curing may occur during prolonged stirring, making it difficult to obtain a qualified sealant and making it difficult to apply.

[0062] According to an embodiment of this application, in step (1), polyorganosiloxane, silicate, barrier agent and filler are first mixed to obtain base material.

[0063] In some embodiments, a first mixing is performed to obtain a base material, which may be carried out in a kneader to make the obtained base material more uniform.

[0064] In some embodiments, the temperature of the first mixing is 90-120°C, such as 90°C, 100°C, 110°C, 120°C, etc.

[0065] In some embodiments, the first mixing time is 1-3 hours, such as 1 hour, 2 hours, 3 hours, etc.

[0066] In some embodiments, the first mixing is carried out under a vacuum of no more than -0.095 MPa.

[0067] According to an embodiment of this application, in step (2), the base material and the crosslinking agent are mixed a second time to obtain a mixture.

[0068] In some embodiments, a second mixing is performed to obtain a mixture, wherein the base material and crosslinking agent are mixed in a planetary mixer.

[0069] Optionally, the second mixing time is 20-40 minutes, for example, 20 minutes, 30 minutes, 40 minutes, etc.

[0070] According to an embodiment of this application, in step (3), the mixture is mixed with a coupling agent and a catalyst in a third mixing process to obtain a sealant.

[0071] In some embodiments, coupling agents and catalysts are added to a planetary mixer containing the mixture to obtain a sealant.

[0072] In some embodiments, the first mixing time is 20-40 minutes, such as 20 minutes, 30 minutes, 40 minutes, etc. In this way, the coupling agent and the crosslinking agent are not added in the same step, which can reduce the overall stirring time of the three and minimize the chance of curing during stirring.

[0073] In some embodiments, the first mixing is carried out under a vacuum of no more than -0.095 MPa.

[0074] A third aspect of this application provides the application of the sealant of the first aspect or the sealant prepared by the method of the second aspect in the sealing of solar photovoltaic modules used at sea. This sealant has good salt spray barrier properties, providing good protection for solar photovoltaic products used at sea.

[0075] The sealant is used in the frame sealant part of offshore photovoltaic modules, filling the gap between the photovoltaic laminate and the profile to play a role in bonding and sealing.

[0076] Exemplary embodiments according to this application will now be described in more detail. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.

[0077] Example 1 (1) Hydroxyl-terminated polydimethylsiloxane, kaolin, silane-modified hydroxide, calcium carbonate, and silica were mixed to obtain a base material; wherein, 45 parts of hydroxyl-terminated polydimethylsiloxane had a viscosity of 20000 mPa·s; 42 parts of nano-calcium carbonate had a particle size of 60 nm; and 3 parts of silica had a specific surface area of ​​200 m². 2 / g; 10 parts of silane-modified magnesium hydroxide, particle size 5um; 10 parts of kaolin, particle size 20μm.

[0078] (2) The base material and the crosslinking agent are mixed for the second time to obtain a mixture; the crosslinking agent is 4 parts, of which 2.5 parts are tetrabutylone oxime silane and 1.5 parts are vinyltributylone oxime silane.

[0079] (3) The mixture is mixed with the coupling agent and the catalyst in a third mixing process to obtain a sealant. The coupling agent is 1 part, of which N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 0.8 parts and amino coupling agent oligomer (JH-AP11) is 0.5 parts; the catalyst is 0.08 parts and dibutyltin dilaurate is 0.

[0080] Examples 2 and 3 The sealant was prepared in accordance with the method of Example 1, except that the weight parts of hydroxyl-terminated polydimethylsiloxane were 40 parts and 60 parts, respectively.

[0081] Examples 4 and 5 The sealant was prepared in accordance with the method of Example 1, except that the viscosities of the hydroxyl-terminated polydimethylsiloxane were 10000 mPa·s and 50000 mPa·s, respectively.

[0082] Example 6 The sealant was prepared according to the method of Example 1, except that 26 parts of calcium carbonate with a particle size of 60 nm were used.

[0083] Example 7 The sealant was prepared according to the method of Example 1, except that 42 parts of calcium carbonate with a particle size of 100 nm were used.

[0084] Example 8 The sealant was prepared according to the method in Example 1, except that 3 parts of precipitated silica were used, and the specific surface area was 250 m². 2 / g.

[0085] Examples 9 and 10 The sealant was prepared in accordance with the method of Example 1, except that the weight parts of silane-modified magnesium hydroxide were 5 parts and 15 parts, respectively.

[0086] Example 11 The sealant was prepared in accordance with the method of Example 1, except that 5 parts of mica with a particle size of 20 μm were used.

[0087] Example 12 The sealant was prepared in accordance with the method of Example 1, except that 15 parts of mica with a particle size of 20 μm were used.

[0088] Example 13 The sealant was prepared according to the method described in Example 1, except that it contained 50 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 30,000 mPa·s; 35 parts of nano-calcium carbonate with an average particle size of 100 nm; and 2 parts of silica with a specific surface area of ​​150 m². 2 / g; 8 parts of silane-modified magnesium hydroxide, with an average particle size of 8 μm; 5 parts of silicate, kaolin, with an average particle size of 10 μm; 5 parts of crosslinking agent, including 3.5 parts of methyl tributanone oxime silane and 1.5 parts of vinyl tributanone oxime silane; 1.5 parts of coupling agent, including 1 part of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.8 parts of amino coupling agent oligomer (JH-AP11); 0.12 parts of catalyst, dibutyltin dilaurate.

[0089] Example 14 The sealant was prepared according to the method described in Example 1, except that it contained 40 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 10000 mPa·s; 35 parts of nano-calcium carbonate with an average particle size of 80 nm; and 5 parts of silica with a specific surface area of ​​250 m². 2 / g; 15 parts of silane-modified magnesium hydroxide, with an average particle size of 2µm; 10 parts of silicate, kaolin, with an average particle size of 30µm; 4 parts of crosslinking agent, including 3 parts of tetrabutylone oxime silane and 1 part of vinyltributylone oxime silane; 1.2 parts of coupling agent, including 0.5 parts of γ-aminopropyltriethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and 0.2 parts of amino coupling agent oligomer (JH-AP11); 0.1 parts of catalyst, dibutyltin dilaurate.

[0090] Example 15 The sealant was prepared according to the method described in Example 1, except that it contained 54 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 20,000 mPa·s; 30 parts of nano-calcium carbonate with an average particle size of 80 nm; and 1 part of silica with a specific surface area of ​​200 m². 2 / g; 5 parts of silane-modified magnesium hydroxide with an average particle size of 5 μm; 4.5 parts of crosslinking agent, including 0.5 parts of methyl tributanone oxime silane, 3 parts of tetrabutanone oxime silane, and 1 part of vinyl tributanone oxime silane; 1.3 parts of coupling agent, including 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.8 parts of amino coupling agent oligomer (JH-AP11); 0.1 parts of catalyst, dibutyltin dilaurate.

[0091] Example 16 The sealant was prepared according to the method of Example 1, except that it contained 50 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 30,000 mPa·s; 35 parts of nano-calcium carbonate with an average particle size of 100 nm; and 2 parts of silica with a specific surface area of ​​150 m². 2 / g; 8 parts of silane-modified magnesium hydroxide; average particle size 30um; 5 parts of kaolin, average particle size 10um; 5 parts of crosslinking agent, including 3.5 parts of methyl tributanone oxime silane and 1.5 parts of vinyl tributanone oxime silane; 1.5 parts of coupling agent, including 1 part of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.8 parts of amino coupling agent oligomer (JH-AP11); 0.12 parts of catalyst, dibutyltin dilaurate.

[0092] Comparative Example 1 The sealant was prepared according to the method of Example 1, except that it contained 45 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 20,000 mPa·s; 32 parts of nano-calcium carbonate with an average particle size of 60 nm; and 3 parts of silica with a specific surface area of ​​150 m². 2 / g; 0 parts of silane-modified magnesium hydroxide; 10 parts of silicate, kaolin, average particle size 20um; 4 parts of crosslinking agent, including 2.5 parts of tetrabutylone oxime silane and 1.5 parts of vinyltributylone oxime silane; 1 part of coupling agent, including 0.8 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.5 parts of amino coupling agent oligomer (JH-AP11); 0.08 parts of catalyst, dibutyltin dilaurate.

[0093] Comparative Example 2 The sealant was prepared according to the method described in Example 1, except that it contained 40 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 10000 mPa·s; 35 parts of nano-calcium carbonate with an average particle size of 80 nm; and 5 parts of silica with a specific surface area of ​​250 m². 2 / g; 15 parts of silane-modified magnesium hydroxide with an average particle size of 2µm; 4 parts of crosslinking agent, including 3 parts of tetrabutylone oxime silane and 1 part of vinyltributylone oxime silane; 1.2 parts of coupling agent, including 0.5 parts of γ-aminopropyltriethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and 0.2 parts of amino coupling agent oligomer (JH-AP11); 0.1 parts of catalyst, dibutyltin dilaurate.

[0094] The sealants of the above embodiments and comparative examples were tested as follows, and the test results are shown in Table 1.

[0095] (1) The hardness of the silicone was tested according to GB / T 531; (2) The tensile strength of silicone was tested according to GB / T 528; (3) The shear strength of silicone (anodized aluminum profile) was tested according to GB / T 7124. (4) The water vapor transmission rate of silica gel was tested according to GB / T 1037; (5) The salt spray corrosion resistance of silicone was tested according to GB / T 1771-2007. The sample preparation and experimental process for the salt spray test are as follows: The test samples are all steel plates of 150 mm × 100 mm × 1 mm. The surface is cleaned with solvent to remove oil stains and sanded clean. The silicone sealant is applied to the steel plate. The silicone adhesive is evenly applied to the front and back surfaces and sides of the steel plate using a thickness control instrument, so that the silicone adhesive completely covers the steel plate. The thickness of the silicone adhesive is controlled at (150±10) μm. After curing for 14 days under standard test conditions (temperature (23±2)℃, relative humidity (50±5)%), the salt spray test is carried out. It is important to ensure that the silicone is completely cured. The salt spray test is carried out according to GB / T 1771—2007.

[0096] Table 1

[0097] As shown in Table 1, the silicone photovoltaic sealants of Examples 1-16 exhibit good mechanical and adhesive properties, as well as excellent salt spray corrosion resistance. Under a 1500-hour salt spray test, the steel plate surface remained in good condition. In Comparative Example 1, due to the lack of silane-modified magnesium hydroxide, severe rust appeared on the steel plate surface after a 1500-hour salt spray test. Comparative Example 2, while also showing good salt spray corrosion resistance, exhibited slight corrosion after 1500 hours, making its performance less satisfactory. This indicates that the sealant of this application can cure at room temperature, possesses good mechanical, adhesive, and aging resistance properties, and also provides good salt spray protection, thus offering excellent protection for solar photovoltaic products used at sea.

[0098] It should also be noted that the terms "some embodiments," "other embodiments," and "embodiments" used in this application refer to specific features, structures, or characteristics described in connection with those embodiments, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.

[0099] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions of other embodiments.

[0100] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of patent protection of this application. Any equivalent structural or procedural changes made using the content of this application's specification, or any direct or indirect application in other related technical fields, are similarly included within the scope of patent protection of this application.

Claims

1. A sealant, characterized in that, include: Polyorganosiloxanes, fillers, crosslinking agents, coupling agents, catalysts, silicates, and barrier agents, wherein the barrier agents include silane-modified magnesium hydroxide.

2. The sealant according to claim 1, characterized in that, The sealant comprises, by weight, 40-60 parts of polyorganosiloxane, 26-46 parts of filler, 5-15 parts of barrier agent, 5-10 parts of silicate, 3-6 parts of crosslinking agent, 0.5-3 parts of coupling agent, 0.05-0.3 parts of catalyst, and the total amount of the sealant is 100 parts.

3. The sealant according to claim 1 or 2, characterized in that, The polyorganosiloxane includes hydroxyl-terminated polydimethylsiloxane; And / or, the filler includes at least one of calcium carbonate and silica; And / or, the silicates include at least one of kaolinite, mica, and montmorillonite; And / or, the crosslinking agent includes at least one of methyltributanone oxime silane, vinyltributanone oxime silane, and tetrabutanone oxime silane; And / or, the coupling agent comprises at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and amino coupling agent oligomers. And / or, the catalyst comprises at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin dineodecanate.

4. The sealant according to claim 3, characterized in that, The hydroxyl-terminated polydimethylsiloxane has a viscosity of 10,000-50,000 mPa·s.

5. The sealant according to claim 3, characterized in that, The specific surface area of ​​the silica is 150-250 m². 2 / g; And / or, the calcium carbonate has a particle size of 60-100 nm; And / or, the particle size of the silane-modified magnesium hydroxide is 1-10 μm; And / or, the silicate has a particle size of 5-30 μm.

6. A method for preparing a sealant, characterized in that, include: The polyorganosiloxane, silicate, barrier agent and filler are first mixed to obtain the base material; The base material is mixed with the crosslinking agent in a second mixing process to obtain a mixture; The mixture is then further mixed with a coupling agent and a catalyst to obtain a sealant.

7. The method according to claim 6, characterized in that, The first mixture satisfies at least one of the following conditions: Temperature 90-120℃; The vacuum level is not higher than -0.095 MPa; Time: 1-3 hours.

8. The method according to claim 6, characterized in that, The second mixing time is 20-40 minutes.

9. The method according to claim 6, characterized in that, The third mixture satisfies at least one of the following conditions: The vacuum level is not higher than -0.095 MPa; Time: 20-40 minutes.

10. The application of the sealant according to any one of claims 1-5 or the sealant prepared by the method according to any one of claims 6-9 in the sealing of solar photovoltaic modules for marine use.